SENGKETA DAGANG TIONGKOK-AUSTRALIA PADA PRODUK BARLEY DI WORLD TRADE ORGANIZATION (WTO) PADA TAHUN 2020-2023 - Putri, Deska Nindia; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The trade dispute between Australia and China, arising from China’s imposition of anti-dumping duties of 73.6% and countervailing duties of 6.9%, escalated tensions and prompted Australia to file a complaint with the World Trade Organization (WTO). This research is analyzed using the international regime theory developed by Robert O. Keohane, with the level of analysis focused on nation-states. The research adopts a qualitative approach with a case study method. Data were collected through primary sources from official websites and secondary sources from various literature as supporting materials. The findings show that the WTO's trade dispute settlement mechanism through the Dispute Settlement Body (DSB) consists of several stages consultation request, panel establishment, panel report, appeal to the Appellate Body, and implementation. In August 2023, China revoked the anti-dumping duties on Australian barley, followed by Australia's decision to withdraw its complaint. Both countries officially informed the DSB that the dispute had been resolved amicably, and the Panel declared its task completed. Keywords: World Trade Organization, Dispute Settlement Body, Trade Dispute, Anti-Dumping Duties, Countervailing Duties.